Implementation of MIMO OFDM NOMA System using Iterative Algorithm. Issue 1 (July 2021) - Anil, S; Pappa, M; Ramesh, C
Abstract: In this modern world, technology has improved a lot and wireless communications are much necessary. MIMO wireless technology is very much essential for providing increased connectivity and spectral efficiency combined with the reliability of advanced connectivity using what were previously considered as interference paths. The multiple access system is considered such that they provide the different methods in communication for multi-users. In this work, the iterative algorithm is used such that it helps in defining random array of signals and assigning the phase to the given measured amplitude. Different types of multiple access systems such as Non-Orthogonal multiple access (NOMA), Orthogonal multiple access (OMA) and Adaptive Orthogonal multiple access (AOMA)which are used to analyze transmission of multiple data stream over power domain in the presence of AWGN and Rayleigh channel. The data transmitted over the channel may vary due to some interference on its path. The signal strength is calculated in the receiver using the fading channel and the other noises that gets added in the channel. MATLAB software tool is used for simulation and the performance analysis in terms of average sum value i.e. the signal strength with respect to SNR for all the above mentioned multiple access techniques is compared. The simulation results clearly exhibits that NOMA outperforms the other two cases and is one of the promising technology for fifth generation wireless communications.